Effectiveness of the early visual stimulation in children with amblyopia from "Pulgarcito" Day-care Center - Nadia I. Iglesias Guirado; Danay Duperet Carvajal; Rebeca Pérez Sánchez; Grisel Frómeta Rivaflechas (Centro Provincial de Información de Ciencias Médicas, 2016)
A therapeutic intervention study in 128 amblyopic children, belonging to "Pulgarcito" Special Care Day-care Center in Santiago de Cuba was carried out from September, 2013 to July, 2014, with the aim of demonstrating the effectiveness of the early visual stimulation and to develop abilities on this respect. There were not significant differences between both sexes. Strabismus constituted the first cause of amblyopia and better results were obtained in the early treated children. The early stimulation was effective to develop abilities in the visual order, by means of a medical - pedagogical treatment that favored the incorporation from these children to the family, school and society in a harmonic way. It was recommended to make an screening in children under 2 years who don´t attend day-care centers to diagnose amblyopia early and this way to control the avoidable blindness.